Márquez de la Plata, Lucía (traducción); Ballesteros González, Antonio (edición); Shelley, Mary (autora). El último hombre. Madrid, Akal, 2020. ISBN: 978-84-460-4856-5. 576 páginas - Lucendo Lacal, Santiago (Investigaciones Feministas, 2022)
Reseña de la obra de Márquez de la Plata, Lucía (traducción); Ballesteros González, Antonio (edición); Shelley, Mary (autora). El último hombre. Madrid, Akal, 2020. ISBN: 978-84-460-4856-5. 576 páginas